Elastomeric skin selection for a fluid‐filled artificial fingertip. Issue 6 (7th June 2012) - Roy, Dipayon; Wettels, Nicholas; Loeb, Gerald E.
Abstract Biomimetic fingertips for robots and prostheses need to combine compliant grip and tactile sensing with robustness in diverse environments. We have evaluated materials for use in a compliant, fluid‐filled artificial fingertip that incorporates multimodal sensing of contact, texture and thermal properties. A variety of silicone elastomers were tested for hardness, wear‐rate, and stress–strain relationships. Diffusion rates of several aqueous and nonaqueous solvents through elastomeric membranes were analyzed to ensure that the sensor could maintain proper fluid volume and function for an extended period. A solution of sodium bromide in poly(ethylene glycol)‐200 and water combined with a Silastic S silicone elastomeric cosmesis produced a stable and robust solution. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013